2011
DOI: 10.1007/s12104-011-9293-6
|View full text |Cite
|
Sign up to set email alerts
|

Backbone assignment and secondary structure of the PsbQ protein from Photosystem II

Abstract: PsbQ is one of the extrinsic proteins situated on the lumenal surface of photosystem II (PSII) in the higher plants and green algae. Its three-dimensional structure was determined by X-ray crystallography with exception of the residues 14-33. To obtain further details about its structure and potentially its dynamics, we approached the problem by NMR. In this paper we report (1)H, (15)N, and (13)C NMR assignments for the PsbQ protein. The very challenging oligo-proline stretches could be assigned using (13)C-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…means that this peak could not be assigned) 26b. The 3D spectra were obtained in the same amount of time by acquiring a different number of data points in the indirect dimensions (TD1=54 and TD2=96 using the standard sequence and TD1=TD2=96 using MQD,).…”
Section: Resultsmentioning
confidence: 99%
“…means that this peak could not be assigned) 26b. The 3D spectra were obtained in the same amount of time by acquiring a different number of data points in the indirect dimensions (TD1=54 and TD2=96 using the standard sequence and TD1=TD2=96 using MQD,).…”
Section: Resultsmentioning
confidence: 99%
“…Cloning, overexpression and purification of uniformly doubly labeled 15 N, 13 C PsbQ from Spinacia oleracea in E. coli were described previously . The samples for NMR spectroscopy contained 800 µM 15 N, 13 C PsbQ, 20 m M Na 2 HPO 4 , 50 µM NaN 3 , 1 m M EDTA (pH = 7.0) in H 2 O: 2 H 2 O 90:10.…”
Section: Methodsmentioning
confidence: 99%
“…Since this cross‐linked site of PsbQ is not visible in the electron density map, it was supposed that the N‐terminal stretch of free PsbQ is very flexible and probably extended in solution . Previous NMR studies of the secondary structure of PsbQ in solution indicated some residual order in the so far unresolved dynamic N‐terminal region which was however inconsistent with the short parallel β‐sheet (I5‐V7 and F38‐L40) reported in the crystallographic structure …”
Section: Introductionmentioning
confidence: 93%
“…Carbon‐13 direct‐detection NMR has proven to be very valuable for studying IDPs/IDRs . In particular, the detection of carbonyl carbon atoms (C′) constitutes a particularly useful tool for detection of proline residues . In this category, the simplest yet most effective experiment is the 2D CON in which the correlations between backbone carbonyl carbon and nitrogen of neighboring residues are detected .…”
Section: Figurementioning
confidence: 99%